Eksplorasi Perasaan Ibu yang Mengalami Stres Pasca Abortus Spontan di RSUD Cilacap - Ningtyas, Ratna; Nani, Desiyani; Swasti, Keksi Girindra (Jurnal Keperawatan Soedirman, 2010)
Pregnancy was a natural condition which was desired by a women, but sometimes the problem of pregnancy occurred unpredictable, such as spontaneous abortion. Women who got spontaneous abortion tends to have high risk psycological nuisance after abortion, which is stress after abortion. This research aimed to explore of motherï¿½s feeling and the factors that caused to stress spontaneous after abortion at regional hospital of Cilacap regency. The method used on this research was qualitative descriptive. The research was done at four districts of reginal hospital in Cilacap regency working area. The districts were Gunung Sumping Gumilir, Jeruk Legi, and Donan. There were five persons as the participants who got stressed after spontaneous abortion. The result of the research showed that the factor of age could cause tostress because the old age was so much harder and at risk to have child. Factors caused to spontaneous abortion on mother after abortion was the cause to pregnancy traume and cause to pathologist of motherï¿½s uterus. The low economic level could cause to stress. Someone whose the economic status was low, could support them to get harder stressed.so much easily. The factor of pregnancy status could cause to stress, abortion of the first baby made women see the importance of pregnancy status to become a mother. So that, abortion of the first child was very special looses. The factor of pregnancy age could cause to stress toward the pregnancy age that was so much higher if they got spontaneous abortion caused to stress spontaneous after abortion. The age that was getting older, things caused to abortion, low economic level, the pregnancy status of the first child, and the pregnancy period could cause to make stress on women of spontaneous after abortion at regional hospital in Cilacap regency working area.